The p75 neurotrophin receptor in cells of oral mucosal epithelium - Bryja, A; Jankowski, M; Dyszkiewicz-Konwińska, M; Piotrowska-Kempisty, H; Antosik, P; Bukowska, D; Bruska, M; Nowicki, M; Kempisty, B (Journal of Biological Regulators & Homeostatic Agents, 2018)
The p75 neurotrophin receptor (p75NTR) can play different roles in cells. This protein can on the one hand act in the regulation of cell growth and survival, while being an apoptosis inducing factor in different contexts. p75NTR regulates cell cycle not only in nerve cells but also in epithelial oral mucosal cells. In the former, neurotrophin-p75NTR signaling affects cell growth and survival. Recent studies showed that p75NTR is expressed in basal cells of oral mucosal epithelium and can be used as one of the markers of epithelial stem/progenitor cells. This role of p75NTR can be utilised in aspects such as tissue engineering and gene therapy. One of the examples of clinical use of cultivated oral mucosal cells is ocular surface reconstruction. p75NTR can be a significant marker of stem cells in studies of epithelial tissues, especially when the cells will exhibit other specific markers, such as CK13, CK14 and PCNA..
Keywords: Receptor, Nerve Growth Factor; Neurons; lidé; Signal Transduction; ústní sliznice; signální transdukce; epitel; neurony; Humans; nízkoafinní receptor faktorů růstu nervů; Epithelium; Mouth Mucosa